DIGITAL CONTACT POTENTIAL PROBE IN STUDYING THE DEFORMATION OF DIELECTRIC MATERIALS - Pantsialeyeu, Kanstantsin; Zharin, Anatoly; Gusev, Oleg; Vorobey, Roman; Tyavlovsky, Andrey; Tyavlovsky, Konstantin; Svistun, Aliaksandr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2020)
The paper reviews the results of a study on the surface electrostatic charges of dielectrics obtained using the contact potential difference (CPD) technique. Initially, the CPD technique was only applied to the study of metal and semiconductor surfaces. The conventional CPD measurement technique requires full compensation of the measured potential that, in the case of dielectrics, could reach very high values. Such high potentials are hard to compensate. Therefore, the conventional CPD method is rarely applied in the study of dielectric materials. Some important improvements recently made to the CPD measurement technique removed the need for compensation. The new method, which does not require compensation, has been implemented in the form of a digital Kelvin probe. The paper describes the principles of the non-compensation CPD measurement technique which was developed for mapping the electrostatic surface charge space distribution across a wide range of potential values. The study was performed on polymers such as low-density polyethylene (LDPE) and polytetrafluoroethylene (PTFE).